DEVELOPMENT ANALYSIS OF MULTIPOINT VIDEO CONFERENCING IN EDUCATION - Sukmandhani, Arief Agus; Mansuan, Melki Sadekh; Lokaadinugroho, Indrabudhi; Maryam, Siti (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2019)
In this modern era, people can do meetings by doing video conferencing. By doing video conferencing we can reach our colleagues who are geographically far from us in real time, as if we are close to them through video and audio visual. it's just that sometimes the capacity of video conferencing tools becomes an obstacle in doing conference simultaneously for multiple locations. Video conferencing between three or more locations is possible through the Multipoint Control Unit (MCU) system. This research was conducted at one of the educational institutions which had several branches spread in various locations and each location had a video conference tool. MCU system that was used previously is the sx20 telepresence which can only accommodate 3 video conference locations simultaneously. from this problem this educational institution developed a new MCU system using Acano. By using this Acano system can support HD quality video so that video and audio can be clearly displayed.